Current concepts in voiding dysfunction and dysfunctional voiding: A review from a urogynaecologist's perspective - Debjyoti Karmakar; Jai B Sharma (Wolters Kluwer Medknow Publications, 2014)
Background: Female voiding dysfunction is a complex disorder, lacks definition, and is poorly understood and difficult to manage. Causes of Female Voiding Dysfunction: As there is no agreed classification of female voiding dysfunction, it is important to identify the several potential factors that might cause voiding dysfunction, namely anatomic, neurogenic, pharmacologic, endocrine, pharmacological and other causes. Presentation and Clinical Evaluation: Traditional and novel techniques are available and the importance and diagnostic dilemma related to these conditions need to be understood. We conclude by emphasizing the need to simplify the diagnosis and nomenclature of these conditions from a more clinical point of view as against an investigational perspective.